Human impact on C/N/P accumulation in lake sediments from northeast China during the last 150 years - Bao, Kunshan; Zhang, Yifeng; Zaccone, Claudio; Meadows, Michael E. (Environmental pollution (1987), 2021)
Lakes and lake sediments are significant components of the global carbon (C) cycle, and may store very large amounts of organic matter. Carbon sequestration in lakes is subject to substantial temporal and spatial variation and may be strongly affected by human activities. Here, we report accumulation rates (AR) of organic C (OC), total nitrogen (TN) and total phosphorous (TP), and investigate their responses to anthropogenic impact over the past 150 years by analyzing 62 sediment cores from 11 shallow lakes in the Songnen Plain, northeast China. From the center of each of the lakes, we selected one master core for age determination by 210Pb and 137Cs radioisotopes. The contents of OC, TN, TP, dry bulk density and mass specific magnetic susceptibility were then determined for all cores. The regional OCAR, TNAR and TPAR up-scaling from the multiple cores yielded mean values of 51.63 ± 15.13, 2.50 ± 0.98, and 0.90 ± 0.21 g m−2 yr−1, respectively. Nutrient AR in the studied lakes increased by a factor of approximately 2 × from the middle 19th century to the 1950s, and approximately 5 × after the 1950s. Elemental ratios show that the increase in OCAR is mainly the result of C autogenesis from the growth of aquatic plants stimulated by agricultural intensification, including increased chemical fertilizer application and farmland expansion. Significantly enhanced nutrient burial by these lakes after the 1950s resulted from increased anthropogenic impacts in northeast China. More sustainable agricultural practises, including a decrease in P fertilizer use, would result in a lowering of OCAR, TNAR and TPAR in the future. [Display omitted] •Accumulation rates of C/N/P were reconstructed through 11 age-dated lake sediments in NE China.•Mean accumulation rates for organic C, total N and total P are ca. 52, 2.5, and 0.9 g m−2 yr−1, respectively.•Nutrient accumulation rates increased ∼2 × from the middle 19th century to the 1950s, and ∼5 × after 1950.•Enhanced nutrient burial in these lakes after the 1950s are due to increased anthropogenic impacts.•More sustainable agricultural practises used during the last years would result in lower accumulation rates of C/N/P. Anthropogenic impacts increased ∼2 × nutrient burial in the Songnen Plain lakes of northeast China from the middle 19th century to the 1950s, and ∼5 × after 1950.